Art Performance Management (Pegas) at SMA Negeri 1 Pamekasan - Apriliandini Savitri; Setyo Yanuartuti (PT. Anagata Sembagi Education, 2024)
Art Performance (Pegas) is an annual school activity and a school flagship activity carried out by class X students of SMA Negeri 1 Pamekasan. The purpose of this research is to describe the management of art performance (pegas) which consists of production management and artistic management and to find out the results of management on art performance (pegas). This research uses a qualitative descriptive approach, data collection using observation techniques, interviews, and documentation. Data analysis through several stages such as data collection, data reduction, data presentation, and conclusion drawing. Data validity uses source triangulation and technique triangulation. The results showed that the management of art performances (pegas) managed by class X students consisted of production management and artistic management by applying management functions, namely planning, organizing, mobilizing, and supervising. The results of the art performance management (pegas) can be seen in the success of the implementation of the art performance (pegas) such as the continuity of the event, the presentation of the work, the audience who attended, and funding or sponsorship. The implementation of the art performance (pegas) was carried out well with the existence of management and the application of management functions so that the art performance (pegas) became effective and efficient.